Typologies of 20-Minute Neighbourhoods, Active Transport Use, and Spatial Spillovers - Liton Kamruzzaman (Findings)
20-minute neighbourhoods aim to promote active transport (AT) use by providing amenities locally. Using compactness and directional distribution of amenities, threshold population, and street patterns, this study derives five different typologies of 20-minute neighbourhoods: 1) Isolated and circular; 2) Semi-compact and semi-linear; 3) Compact and linear; 4) Organic; and 5) Semi-compact and circular. Spatial autoregressive models show that all types of 20-minute neighbourhoods promote people to use AT to work. However, Typology 5 has the largest effects, directly encouraging 7% more people to use AT locally and indirectly leading 18% more people to use AT in the neighbouring areas.